2007
DOI: 10.1161/atvbaha.107.142539
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protease Activated Receptor 1 and 2 Signaling in Hypoxia-Induced Angiogenesis

Abstract: Objective-Tissue factor (TF) initiates coagulation and indirectly triggers thrombin-dependent protease activated receptor (PAR) signaling. The TF-VIIa complex also directly cleaves PAR2 and promotes angiogenesis in vitro in TF cytoplasmic domain-deleted (TF ␦CT ) mice. Here we address the effect of PAR1 and PAR2 deficiency on angiogenesis in vivo. Methods and Results-In hypoxia-driven angiogenesis of oxygen induced retinopathy (OIR), wild-type, PAR1Ϫ/Ϫ , PAR2 Ϫ/Ϫ , and TF ␦CT mice showed a comparable regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 31 publications
(41 reference statements)
7
98
0
4
Order By: Relevance
“…21) Recently, Uusitalo-Jarvinen et al have shown using genetically deficient mice that PAR1 and PAR2 play roles in hypoxia-driven angiogenesis and that PAR2 signaling is sufficient for this proangiogenic effect. 39) In the present study, the factor Xa inhibitor fondaparinux suppressed both glomerular hypertrophy and hypervascularity in db/db mice. Taken together, it is tempting to speculate that fondaparinux inhibits glomerular hypertrophy by the suppressing angiogenesis through PAR2 regulation.…”
Section: Discussionsupporting
confidence: 52%
“…21) Recently, Uusitalo-Jarvinen et al have shown using genetically deficient mice that PAR1 and PAR2 play roles in hypoxia-driven angiogenesis and that PAR2 signaling is sufficient for this proangiogenic effect. 39) In the present study, the factor Xa inhibitor fondaparinux suppressed both glomerular hypertrophy and hypervascularity in db/db mice. Taken together, it is tempting to speculate that fondaparinux inhibits glomerular hypertrophy by the suppressing angiogenesis through PAR2 regulation.…”
Section: Discussionsupporting
confidence: 52%
“…34 Both PAR-1 and PAR-2 play roles in hypoxia-driven angiogenesis, and PAR-2 signaling is sufficient for the pro-angiogenic effect. 35 In the present study, fondaparinux suppressed angiogenesis; meanwhile, the expression and signaling of PAR-1 and PAR-2 were reduced in the fondaparinux group. Taken together, it is tempting to speculate that fondaparinux might contribute to the stability of the plaque by inhibiting angiogenesis through PAR-1/2 regulation.…”
Section: Fondaparinuxsupporting
confidence: 49%
“…The absence of the cytoplasmic domain of TF was previously associated with a diminished inflammatory response in a murine arthritis model (38). However, studies performed in a mouse model of oxygen-induced retinopathy showed that loss of the TF cytoplasmic domain resulted in increased angiogenesis mediated by TF/FVIIa signaling through PAR2 (39).…”
Section: Figurementioning
confidence: 99%